1998
DOI: 10.1016/s0082-0784(98)80116-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiative emission and absorption on the propagation and extinction of premixed gas flames

Abstract: Premixed gas flames in mixtures of CH 4 , O 2 , N 2 and CO 2 were studied numerically using detailed chemical and radiative emission-absorption models to establish the conditions for which radiatively-induced extinction limits may exist independent of the system dimensions. It was found that reabsorption of emitted radiation led to substantially higher burning velocities and wider extinction limits than calculations using optically-thin radiation models, particularly when CO 2 , a strong absorber, is present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Rather, it is spectral dependent and has temperature and pressure broadening. Ju and his coworkers [20,21] first used the non-gray statistical narrow band (SNB) model in studying the CO 2 diluted propagating flames and showed that a ''fundamental'' flammability limit exists because of the emission-absorption spectra difference between the reactants and products and band broadening. This model was later used in flame balls [22] and high pressure planar flames [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, it is spectral dependent and has temperature and pressure broadening. Ju and his coworkers [20,21] first used the non-gray statistical narrow band (SNB) model in studying the CO 2 diluted propagating flames and showed that a ''fundamental'' flammability limit exists because of the emission-absorption spectra difference between the reactants and products and band broadening. This model was later used in flame balls [22] and high pressure planar flames [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, even the prediction was better than that of optically thin model [8,9], it still could not reproduce the experimental data [7]. Moreover, because of the limitation of computation time, radiation modeling [20] still used the gray assumption on each spectral line and was limited to one-dimensional (1D) planar flame geometry although many experimental data are from spherical flames. More importantly, experimental data of radiation absorption was not available to validate the modeling.…”
Section: Introductionmentioning
confidence: 99%
“…However, a little attempt is made on the issue of flame propagation in the tube/channel with the addition of local heating. It is reported by Ju et al [17] and Chen et al [18] that the self-absorption of radiation emitted from the flame has significant effect on burning velocity and flammability limits. Obviously, this selfabsorption of emitted radiation from the flame is mild while the absorption of an external radiation is strong in nature.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] and their citations). These papers contain interesting findings regarding radiation-induced bifurcations [8] and effects of self-absorption of radiation [9]. Premixed flames are more prone to instability and their radiation signals may be used in a control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] and their citations). These papers contain interesting findings regarding radiation-induced bifurcations [8] and effects of self-absorption of radiation [9].…”
Section: Introductionmentioning
confidence: 99%